PENINGKATAN KINERJA DOSEN MELALUI EFIKASI DIRI, PELATIHAN DAN PRESTASI AKADEMIK DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERATING DI UNIVERSITAS ISLAM SULTAN AGUNG SEMARANG - Widyastuti Widyastuti (Jurnal Riset Bisnis Indonesia, 2015)
This research purpose to conduct a description and analysis of the influence of self-efficacy, training,academic achievement of the performance of lecturers by inserting variable of organizational cultureas a moderating variable. Samples taken as many as 72 of the 262 lecturers with Random Proportionaltechnique. The result have shown that self-efficacy and academic achievement significantlyinfluence the performance of lecturers, while training does not affect the performance of the lecturer.Organizational culture does not strengthen the influence of self-efficacy and performance training forlecturers.Keywords: Self Efficacy, Training, Academic Achievement, Organizational Culture, LecturerPerformance.